2018
DOI: 10.1093/tbm/iby073
|View full text |Cite
|
Sign up to set email alerts
|

Randomized factorial experiment of components of the SmokeFree Baby smartphone application to aid smoking cessation in pregnancy

Abstract: Smartphone applications (apps) might be able to reach pregnant smokers who do not engage with face-to-face support. However, we do not know how far pregnant smokers will engage with smoking cessation apps or what components are likely to be effective. This study aimed to assess pregnant smokers' engagement with the SmokeFree Baby app (v1) and to assess the short-term efficacy of selected components ("modules") for smoking abstinence. Positive outcomes would provide a basis for further development and evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
1
36
1
1
Order By: Relevance
“…One RCT has found that an app acting as a decision aid for smokers interested in stopping smoking resulted in higher 6-month abstinence rates than an information-only app 8 . Another RCT examined the effectiveness of a set of app components as an aid to cessation in pregnant smokers; engagement with the app was low and no specific components were found to increase short-term self-reported abstinence rates 9 . To date, no RCTs have been published comparing apps designed to provide ongoing support for quit attempts with unaided quitting, or more intensive versus less intensive versions of an app.…”
Section: Introductionmentioning
confidence: 99%
“…One RCT has found that an app acting as a decision aid for smokers interested in stopping smoking resulted in higher 6-month abstinence rates than an information-only app 8 . Another RCT examined the effectiveness of a set of app components as an aid to cessation in pregnant smokers; engagement with the app was low and no specific components were found to increase short-term self-reported abstinence rates 9 . To date, no RCTs have been published comparing apps designed to provide ongoing support for quit attempts with unaided quitting, or more intensive versus less intensive versions of an app.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies designed specifically with apps for pregnant smokers [23,24] have reported promising results with digital smoking cessation interventions, but despite their systematic development and usability testing, engagement was low and did not appear to increase smoking abstinence during pregnancy [25]. A recent study seems to show that choice of an app for smoking cessation can be influenced by its immediate appearance and “social successes” [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to internet-based interventions, mobile apps are also suitable for smoking cessation during pregnancy; they are flexible, remote and non-judgmental [4]. However, although such intervention are seem attractive and offer wide reach, at least in theory, there exists only very limited research about their effectiveness for real behaviour [3,4,24].…”
Section: Mobile and Internet Opportunities For Effective Interventionsmentioning
confidence: 99%
“…Importantly, in most countries there is limited availability of evidence-based cessation support, and this includes services dedicated to women who are pregnant and smoking. Digital behaviour change intervention (DBCI) such as websites or smartphone apps could provide behavioural support to pregnant smokers wanting to quit, especially if they cannot or do not want to access traditional face-to-face support, although research on the topic remains limited [2][3][4][5]. To date, no smartphone-based intervention supporting quitting smoking has been developed to support women in Poland to quit.…”
Section: Introductionmentioning
confidence: 99%